2013
DOI: 10.1002/ccd.24983
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic characteristics of femoropopliteal in‐stent restenosis: Association with long‐term outcomes after endovascular intervention

Abstract: Objectives The purpose of this study was to identify the relationship between angiographic patterns of restenosis and outcomes after endovascular treatment of femoro-popliteal in-stent restenosis (FP-ISR). Background ISR is a frequent clinical problem after femoro-popliteal stenting. Methods This was a single center study of all endovascular interventions for FP-ISR from 2006 to 2012. Class I ISR was defined as focal lesions ≤50 mm; Class II ISR as lesions > 50 mm; and Class III ISR as stent chronic total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 22 publications
3
37
1
Order By: Relevance
“…Among patients with in-stent restenosis, 108 patients with 119 lesions (mean lesion length 133 mm) were treated with Zilver DES. Primary patency was 78.8% at 1 year, which compares favorably with previously reported outcomes of other treatment modalities for femoropopliteal in-stent restenosis [40,41]. These preliminary results suggest that Zilver DESs may have a significant role in the treatment of lesions that are otherwise at high risk of restenosis with standard therapies.…”
Section: Drug-eluting Stentssupporting
confidence: 82%
See 1 more Smart Citation
“…Among patients with in-stent restenosis, 108 patients with 119 lesions (mean lesion length 133 mm) were treated with Zilver DES. Primary patency was 78.8% at 1 year, which compares favorably with previously reported outcomes of other treatment modalities for femoropopliteal in-stent restenosis [40,41]. These preliminary results suggest that Zilver DESs may have a significant role in the treatment of lesions that are otherwise at high risk of restenosis with standard therapies.…”
Section: Drug-eluting Stentssupporting
confidence: 82%
“…Ultimately, direct comparisons of newer technologies will be necessary. Such studies will also have to consider the cost and outcomes of in-stent restenosis that has poor long-term patency and remains difficult to treat despite available technologies [41]. Whether drug-coated balloons will disrupt or diminish the use of nitinol stents also remains an important unanswered question in the optimal treatment of patients with femoropopliteal disease.…”
Section: Expert Commentarymentioning
confidence: 97%
“…One recent study showed high rates of restenosis and recurrent occlusion for class II and III FP-ISR even with the use of adjunctive devices and provisional stenting, thus raising concern that currently available technologies may not improve outcomes of FP-ISR compared with balloon angioplasty alone. 28 Given that in-stent occlusion contains both neointima and thrombus, laser atherectomy, by debulking the neointima and thrombus and inhibiting platelet aggregation, offers a potentially promising therapeutic avenue for treatment of FP-ISR. 16 Several studies have examined the use of laser atherectomy for treatment of FP-ISR, but those studies did not specifically analyze the association of angiographic characteristics with outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up to that study, we evaluated a multimodality approach to the treatment of FP-ISR. 7 Seventy-five patients underwent endovascular treatment of FP-ISR using a variety of adjunctive devices, including laser atherectomy, excisional atherectomy, and repeat stenting. Despite the use of these adjunctive therapies in the majority of cases, rates of repeat restenosis at 2 years were 39% for class I ISR, 67% for class II ISR, and 72% for class III ISR.…”
Section: Article See P 2230mentioning
confidence: 99%